(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article discusses methods of activating school-age students in the classroom, ways to increase the effectiveness of their knowledge through the organization of independent work, ways to increase students’ interest in science, and highlights the educational value of independent work.